PS-008 Exposure to vasoconstrictor nasal decongestants in patients with pulmonary arterial hypertension. (24th February 2014) - Perrin, S; Montani, D; Guignabert, C; Savale, L; Sitbon, O; Simmoneau, G; Humbert, M; Chaumais, M
Abstract : Background: Pulmonary Arterial Hypertension (PAH) is a life-threatening lung disorder with no curative options, to which vasoconstriction, in situ thrombosis and intense pulmonary arterial remodelling are key contributors. Although a causal relationship has not been established, the pharmacology of nasal vasoconstrictor decongestants (VCNs) together with a high association between VCN dose and fatality of PAH reported in the literature, have raised the awareness of VCN exposure in PAH. Purpose: To compare VCN exposure between a group of patients with PAH and a control group of persons without PAH. Materials and methods: A monocentric observational and comparative study was conducted in France from 15 December 2012 to 30 July 2013. The study cohorts consisted of 99 patients with idiopathic, heritable or drug-induced PAH or pulmonary veno-occlusive disease and 58 accompanying persons without PAH. Included subjects completed a validated questionnaire. For additional information, the general practitioner and the referral pharmacist were contacted. Results: Median ages were respectively 56.2 and 52.3 years. General characteristics of patients were consistent with data from the literature. Respectively, 71% of patients with PAH and 79% of accompanying persons were exposed to at least one VCN (p > 0.05). In PAH patients with stronger consumption of VCNs, median ages were significantly lower and numbers of women were higher. However, due to bias (cognitive, market, traceability), potential relationships between VCN exposures and PAH could not be accurately assessed. Conclusions: Although additional studies are needed, VCN use is probably not involved at least as a strong signal in PAH. Since VCNs are easily available often in self-medication, proving a causal link is difficult. However, this study has enabled the implementation of a methodology for data collection and signal detection to strengthen the drug monitoring system in the French National PAH Network. No conflict of interest.